The Supply Chain Strategy in Society and Active Longevity in Russia - T.A Burtseva; N.Yu Chausov; S.N Gagarina (International Journal of Supply Chain Management, 2020)
Abstract- Born from multidisciplinary roots that include logistics, marketing, management, and sociology, SCM has developed into a distinct field of study over the past fifty years. SCM theory has only recently reached a state of maturation where it produces operationalisable concepts and tools, but progress is being made in advancing both the overarching field of SCM and the specific issues that fall under the SCM umbrella. The authors investigated supply chain strategy as an active longevity’s policy and quality of life of elderly population in the Russian Federation. Factors of the active longevity and reasons that reduce the level of life quality and society of elderly population in 2014-2016 have been discovered. The offered normative and evaluative model of life quality of elderly population and a list of strategies of active longevity are a novelty of the research. A practical importance of the research results is in the using its results to solve national economic issues and to provide the active longevity in Russia.